EKSTRAKSI ION TEMBAGA(II) DENGAN EMULSI MEMBRAN CAIR MENGGUNAKAN DITIZON SEBAGAI PEMBAWA KATION - Hamzah, Baharuddin; Tuljannah, Naima; Diharnaini, Diharnaini (Jurnal Akademika Kimia, 2013)
The research regarding the extraction of copper ions with liquid emulsion membrane has been done. It used a laboratory experiment method by using dithizone as a carrier compound, paraffin liquid as the membrane, a solution of HCl as an internal phase, Span-60 as surfactant, and a solution of copper(II) as the sample solution. This study was conducted to examine the ability of dithizone as a cation carrier and to determine the optimum conditions for the extraction of copper(II) ions in a solution that includes dithizone concentration and copper(II) ion extraction capacity with liquid membrane emulsion technique. The dithizone concentrations used were 0.005 M, 0.010 M, 0.015 M, 0.020 M, and 0.025 M. On the other hands the copper(II) solution concentrations used were 348 ppm, 512 ppm, 689 ppm, 857 ppm, and 1029 ppm. Concentration of copper(II) ion in external-phase was determined by using SpectroDirect Spectrophotometer. The result showed that the use of 0.020 M dithizone, 50 mL of liquid emulsion membrane could extract 857 ppm copper(II) ions with the extract percentage was 84.13%.